Federal constitutional and statutory rights of teachers (2008)
The purpose of this paper was to consider some rights and freedoms of teachers in Nigerian jurisdiction. The study was aimed at observing some basic constitutional rights and freedoms of teachers in Nigeria. Certain statutory provisions covering the rights and freedoms of teachers in Nigeria were also looked into. It was observed that most of the rights and freedoms of teachers were not hitherto separated or distinguished from the basic rights and freedoms of other workers within the jurisdiction. The study went further to also observe some rights and freedoms of teachers in the United States of America, which is a developed nation vis - a- vis Nigeria, which is yet developing. The rights and freedoms of teachers in the US were couched in specific and general provisions of laws in that jurisdiction, and this could be seen to be protected under various constitutional provisions, states and federal statutes, and states and federal regulations. Though the two nations shared some common grounds as far as teachers' rights, privileges, duties and responsibilities were concerned, there were yet some areas of diversity which might be due to various norms, values and policies esteemed by each nation.